Evaluation of Influential Factors on Curry Puff Packaging Design Using Analytic Hierarchy Process (AHP): A Case Study of La-ngu District, Satun Province - Rattanakool, Tanarat; sukkrajang, kantamon; Kaewdee, Chatchai (Academic Journal of Industrial Technology Innovation, 2024)
This study aims to evaluate the relative importance of factors influencing curry puff packaging design in La-ngu, Satun, Thailand, using the Analytic Hierarchy Process (AHP). Theoretical frameworks on packaging design and consumer behavior were employed to define the involved primary and secondary factors. Five curry puff entrepreneurs in La-ngu were purposively selected based on their expertise and experience in producing and selling curry puffs. Empirical data were collected through in-depth interviews and AHP questionnaires to analyze pairwise comparisons of the identified factors. The results indicated that packaging material (0.384) had the highest weight among the primary factors, followed by branding logo/design style (0.255), packaging color (0.136), label type (0.105), label color (0.062), and packaging information (0.059), respectively. This result indicate that entrepreneurs prioritize on maintaining product quality and freshness of curry puffs through appropriate material selection. Simultaneously, the design of brand/logo plays an important role in establishing brand identity and recognition. Among the secondary factors, plastic material (0.679) was given the highest weight of importance, aligning with the trend of using plastic materials in food packaging industry. The halal certification logo (0.613) was the next most significant secondary factor, reflecting the emphasis on Muslim consumers in the area. Other noteworthy secondary factors included the use of vibrant two – color labels (0.507), direct printing of information on packaging (0.373), and three-color packaging designs (0.276), indicating a focus on attractive design and effective information communication.